2006
DOI: 10.1111/j.1467-9485.2006.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of the Highly Educated: The Role of Gender, Academic Tenure, and Earnings

Abstract: The determinants of job satisfaction are estimated for Ph.D. level scientists in the United States across academic and nonacademic sectors. Female scientists report lower job satisfaction than males in academia but higher job satisfaction than males in the nonacademic sector. Academic scientists with tenure have substantially greater job satisfaction than non-academic scientists but academic scientists without tenure report similar levels of satisfaction as non-academic scientists. Finally, in each sector, job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
118
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 36 publications
7
118
3
2
Order By: Relevance
“…Previous studies have found that PhDs working outside academia are less satisfied with their job than those working in academia (e.g., Bender and Heywood 2006;Moguérou 2002). However, we do not find such an effect of employment sector when type of employment and required educational level are controlled for.…”
Section: Satisfaction With Job Contentcontrasting
confidence: 51%
See 3 more Smart Citations
“…Previous studies have found that PhDs working outside academia are less satisfied with their job than those working in academia (e.g., Bender and Heywood 2006;Moguérou 2002). However, we do not find such an effect of employment sector when type of employment and required educational level are controlled for.…”
Section: Satisfaction With Job Contentcontrasting
confidence: 51%
“…However, the same paper finds that this gender difference, with women being more satisfied, disappears for the highly educated, and for persons in professional and managerial positions. Indeed, studies on the job satisfaction of PhD graduates have found female PhDs to actually be less satisfied (Bender and Heywood 2006;Moguérou 2002). Nationality also matters: US-born science and engineering faculty were found to be more satisfied with their job than foreign-born faculty (Sabharwal 2011).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we only include studies focused on doctorate With regards to gender, the analyses of Moguerou (2002) and Bender and Heywood (2006) show that female doctorate holders have a greater job satisfaction that men. This result is in line with the general evidence usually defined as the 'paradox of the contented female worker': the fact that female employees have higher levels of job satisfaction is related to women's lower expectations (see Clark 1997;Bender et al 2005).…”
Section: Literature Review On the Determinants Of Doctorate Holders' mentioning
confidence: 99%